Evaluation of the Novel 4R Oncology Care Planning Model in Breast Cancer: Impact on Patient Self-Management and Care Delivery in Safety-Net and Non–Safety-Net Centers. Issue 8 (August 2021) - Trosman, Julia R.; Weldon, Christine B.; Rapkin, Bruce D.; Benson, Al B.; Makower, Della F.; Liang, Su-Ying; Kulkarni, Swati A.; Perez, Claudia B.; Lo, Shelly S.; Krueger, Editha A.; Throckmorton, Alyssa D.; Gallagher, Christopher; et al.
Abstract : PURPOSE: Optimal cancer care requires patient self-management and coordinated timing and sequence of interdependent care. These are challenging, especially in safety-net settings treating underserved populations. We evaluated the 4R Oncology model (4R) of patient-facing care planning for impact on self-management and delivery of interdependent care at safety-net and non–safety-net institutions. METHODS: Ten institutions (five safety-net and five non–safety-net) evaluated the 4R intervention from 2017 to 2020 with patients with stage 0-III breast cancer. Data on self-management and care delivery were collected via surveys and compared between the intervention cohort and the historical cohort (diagnosed before 4R launch). 4R usefulness was assessed within the intervention cohort. RESULTS: Survey response rate was 63% (422/670) in intervention and 47% (466/992) in historical cohort. 4R usefulness was reported by 79.9% of patients receiving 4R and was higher for patients in safety-net than in non–safety-net centers (87.6%, 74.2%, P = .001). The intervention cohort measured significantly higher than historical cohort in five of seven self-management metrics, including clarity of care timing and sequence (71.3%, 55%, P < .001) and ability to manage care (78.9%, 72.1%, P = .02). Referrals to interdependent care were significantly higher in the intervention than in the historical cohort along all six metrics, including primary care consult (33.9%, 27.7%, P = .045) and flu vaccination (38.6%, 27.9%, P = .001). Referral completions were significantly higher in four of six metrics. For safety-net patients, improvements in most self-management and care delivery metrics were similar or higher than for non–safety-net patients, even after controlling for all other variables. CONCLUSION: 4R Oncology was useful to patients and significantly improved self-management and delivery of interdependent care, but gaps remain. Model enhancements and further evaluations are needed for broad adoption. Patients in safety-net settings benefited from 4R at similar or higher rates than non–safety-net patients, indicating that 4R may reduce care disparities.